Effects of PCBs, p, p′-DDT, p, p′-DDE, HCB and β-HCH on thyroid function in preschool children. Issue 7 (12th October 2007) - Álvarez-Pedrerol, M; Ribas-Fitó, N; Torrent, M; Carrizo, D; Grimalt, J O; Sunyer, J
Abstract : Objective: Several studies have shown that some organochlorine compounds (OCs) can interfere with the thyroid system. As thyroid hormones (THs) are essential for normal brain development, it is important to study the association between THs and OCs during pregnancy and childhood. We have evaluated the relationship between thyroid function and OCs in preschool children. Methods: Children from a general population birth cohort in Menorca (n = 259), Spain were assessed at the age of 4 years. Concentrations of THs (free T4 and total T3), thyrotropin (TSH) and a range of OCs were measured in peripheral blood. Results: Blood levels of dichlorodiphenyl trichloroethane (p, p′-DDT), β-hexachlorocylcohexane (β-HCH), polychlorinated biphenyls (congeners PCB-138, PCB-153 and PCB-118) were related to lower total T3 levels (p<0.05). In addition, free T4 was inversely associated with PCB-118, while no relationship was found between TSH and any of the measured OCs. Conclusions: This study suggests that even at background levels of exposure, OCs may affect the thyroid system, particularly total T3 levels.